2018
DOI: 10.3389/fpls.2018.00178
|View full text |Cite
|
Sign up to set email alerts
|

Development of Biofortified Maize Hybrids through Marker-Assisted Stacking of β-Carotene Hydroxylase, Lycopene-ε-Cyclase and Opaque2 Genes

Abstract: Traditional yellow maize though contains high kernel carotenoids, the concentration of provitamin A (proA) is quite low (<2 μg/g), compared to recommended level (15 μg/g). It also possesses poor endosperm protein quality due to low concentration of lysine and tryptophan. Natural variant of crtRB1 (β-carotene hydroxylase) and lcyE (lycopene-ε-cyclase) cause significant enhancement of proA concentration, while recessive allele, opaque2 (o2) enhances the level of these amino acids. Development of biofortified mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
77
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 57 publications
10
77
1
1
Order By: Relevance
“…The favorable allele LcyE 3′Indel reduced the ratio of a to b-branch carotenoids by up to 30%, without a notable increase in BC or PVA content. Effectiveness of the CrtRB1-3′TE polymorphism in increasing PVA content was also demonstrated by Zunjare et al (2018). The maximum PVA content that can be achieved by selecting for both the CrtRB1-3'TE and LcyE 3′Indel polymorphisms is unknown, partly because of a large genetic background effect or epistasis .…”
Section: Molecular Breeding For Provitamin a Enrichmentmentioning
confidence: 97%
See 1 more Smart Citation
“…The favorable allele LcyE 3′Indel reduced the ratio of a to b-branch carotenoids by up to 30%, without a notable increase in BC or PVA content. Effectiveness of the CrtRB1-3′TE polymorphism in increasing PVA content was also demonstrated by Zunjare et al (2018). The maximum PVA content that can be achieved by selecting for both the CrtRB1-3'TE and LcyE 3′Indel polymorphisms is unknown, partly because of a large genetic background effect or epistasis .…”
Section: Molecular Breeding For Provitamin a Enrichmentmentioning
confidence: 97%
“…These testing schemes led to the release of 47 PVA-enriched hybrids and synthetics that meet 50-80% of the current PVA breeding target in nine countries, including Zambia, Zimbabwe, Malawi, Tanzania, DRC, Ghana, Mali, and Nigeria (Menkir et al, 2018). In addition, the high PVA inbred lines developed at CIMMYT and IITA have been effectively used as PVA donors by the national maize breeding programs in Asia (e.g., China and India) and Latin America (e.g., Brazil and Panama) to develop improved, nutritionally enriched maize cultivars (Muthusamy et al, 2014;Liu et al, 2015;Zunjare et al, 2018;Goswami et al, 2019;Listman et al, 2019).…”
Section: Nutritionally Enriched Maize Cultivar Releases and Commerciamentioning
confidence: 99%
“…In a recent study, it was demonstrated that PSY protein homeostasis is maintained through the opposite effects of the Clp-protease (CLP) degrading activity and the Or protein that increases the stability of this enzyme, which represents a new post-translational regulatory mechanism of plant carotenoid biosynthesis [178]. were used for breeding of provitamin A biofortified maize hybrids through MAS [185]. In cassava, the allelic variation (Ala > Asp mutation) in PSY leads to enhanced enzymatic activity and, hence, to increased carotenoid accumulation in yellow-rooted cassava varieties with increased provitamin A content [186].…”
Section: Regulation Of Carotenogenesismentioning
confidence: 99%
“…Recovery of recurrent parent genome (RPG) among selected backcross progenies ranged from 89 to 93%. Introgressed progenies possessed high concentration of provitamin A (7.38-13.59 µg/g), compared to 1.65-2.04 µg/g in the recurrent parents (Zunjare et al, 2018). Goswami et al (2019) reported marker-assisted introgression of rare allele of β-carotene hydroxylase (crtRB1) gene into elite quality protein maize inbred for combining high lysine, tryptophan and provitamin A in maize.…”
Section: Improvement Of Provitamin a Carotenoid Content In Maize Thromentioning
confidence: 99%
“…The important basis for these approaches is identification of the key genes regulating carotenoid biosynthesis pathways and a number of functional molecular markers for genes/alleles related to increase in the levels of carotenoids in plants. Some such genes have been identified (Harjes et al, 2008;Yan et al, 2010), applied for gene transfer (Aluru et al, 2008;Zhu et al,2008;Farre et al, 2013;Zanga et al, 2016) and selecting maize lines having high content of provitamin A carotenoids (Muthusamy et al, 2014;Liu et al, 2015;Zunjare et al, 2018). In this article, I will review the recent advances in these two approaches toward biofortification of provitamin A carotenoids, especially, -carotene in maize.…”
Section: Introductionmentioning
confidence: 99%